The Influence Of Liquidity Ratio And Debt To Equity Ratio On Financial Performance Assessment In The Food And Beverage Sub Sector (Survey Of Food And Beverage Issuers Registered On The IDX for the 2020-2022 Period) - Fauziah, Melsy Dinari; Yusnita, Rita Tri; Rahwana, Kusuma Agdhi (Universitas Dehasen Bengkulu, 2024)
The achievements achieved by a company in financial management and the performance conditions of an entity are called financial performance. The aim of this research is to find out how liquidity variables measured by the Current Ratio (CR) and Debt to Equity Ratio (DER) influence financial performance as measured by the Profitability Ratio (ROA) simultaneously or partially. This research uses the annual financial reports of Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022. This research uses a quantitative descriptive approach. The sample selection method used was the purposive sampling method. The sample used is the annual financial report of Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange for 2020-2022. The data source in this research is secondary data in the form of audited financial reports obtained from www.idx.co.id. The data analysis technique used is linear panel data regression using SPSS 26. Based on the research results, it is concluded that liquidity and debt to equity ratio simultaneously have a significant effect on financial performance. Partially, liquidity does not have a significant effect on financial performance. Debt to equity ratio partially does not have a significant effect on financial performance.